Children advertising and toys: a complicated triangle. (Journal of Parents and Teachers, 2014)
The best-selling and most gifted toys for children are not always the best for them to develop. On numerous occasions, we get carried away by advertising and fashions regardless of whether or not toys are suitable for our children. This article exposes toys that were nominated for the Golden Hoops, the prizes for the best toys, and explains the need to buy useful and creative toys.
Keywords: toys; fashions; advertising; best toys; child development.